Modernizing Data Platforms into Cloud for Strategic Advantage with AI - Simi Abdul Shukkoor (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapid evolution of cloud computing and artificial intelligence (AI) has revolutionized the way organizations manage, process, and derive value from their data. Modernizing data platforms by migrating them to the cloud and integrating AI capabilities has emerged as a strategic imperative for businesses seeking to enhance agility, scalability, and innovation. This article explores the transformative potential of cloud-based data platforms augmented by AI, highlighting the strategic advantages they offer. It examines key considerations for modernization, including architectural design, data governance, and AI integration, while addressing challenges such as security, cost management, and organizational change. The article concludes with a forward-looking perspective on how businesses can leverage these technologies to drive competitive advantage in the digital era.